TEACHERS INNOVATION IN CLASS MANAGEMENT TO INCREASE STUDENT LEARNING MOTIVATION IN PANDEMIC ERA - Rodhatul Jennah; Surawan Surawan; Muhammad Yusuf (Proceeding International Seminar of Islamic Studies, 2022)
This article was compiled to describe the innovation of teachers in classroom management to increase the learning motivation of students of class VIII MTs Nurul Yaqin Kuala Kurun in the pandemic era. This article is motivated by a decrease in student learning motivation in the pandemic era. Because learning that was originally face-to-face is diverted by distance learning or online. The method used in this research is a descriptive qualitative method. The results showed that teachers as classroom managers must make innovations that can increase students learning motivation during pandemic era: 1) Create active and fun learning, 2) Build good interpersonal relationships between teachers and students, 3) Hold quizzes, assessments and challenges that trigger the competitive nature of students. During this pandemic, teachers can innovate in the world of education, especially in managing classes that make students excited and motivated. Motivation is what students can follow and receive learning well.Keywords: Innovation; Classroom Management; Learning Motivation; Covid-19 Pandemic